Learner Directed Instruction: Additional Evidences. - Liao, Shu S. (The Accounting Review, 1978)
Abstract ABSTRACT: Empirical evidence of the effectiveness of learner-directed instruction has been somewhat inconclusive. This article reports the results of an experiment utilizing the self-paced, competency-based method, in contrast to the traditional lock-step instructional method. The experiment was designed to examine whether the use of competence-based requirement in the setting of an accounting class will improve students' performance and whether the self-paced format has differential effects on student performance, The analysis of results indicates that the answer to both questions is positive.